Success of Transgenic Bt-hybrid Cotton in Andhra Pradesh State of India - Ravindranath, K.; Reddy, Pocha Brahmananda (International Journal of Bio-resource and Stress Management, 2023)
Cotton is a major commercial fiber crop in India and important crop in countries like USA, Australia. The advent of molecular biology and plant genetic engineering have developed transgenic crop plants which express Bt-insecticidal proteins to agronomi¬cally important levels. Such crop though works effective against bollworms especially the American bollworm with 30% higher yield and 60% reduction on chemicals use on cotton plants but also needs agronomic measures. Cotton plant contains a toxic pigmented chemical Gossypol in various plant parts and seed and is said to act as a deterrent against certain pests. Moreover, 20% of non-Bt-cotton is to be grown in the periphery of Bt-cotton as refugea crop to reduce chance of development of resistance.